2015
DOI: 10.1186/s40814-015-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the collection and assessment of patient-reported outcome data amongst unplanned surgical hospital admissions: a feasibility study

Abstract: BackgroundRandomised controlled trials (RCTs) in surgery can be challenging to conduct, and trials in the emergency surgical setting when patients have unplanned hospital admissions are particularly difficult. One area of challenge is capturing baseline patient-reported outcome (PRO) data. This study examined the feasibility and optimal methods for the collection of baseline and follow-up PRO data in the setting of unplanned surgical hospital admissions.MethodsClinically stable adult patients with unplanned ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
9
2
Order By: Relevance
“…LaCeS has demonstrated that it is possible to collect high-volume, good-quality clinical and patient-reported outcome data in the emergency setting both at baseline and during follow-up. Although attrition was noted during follow-up with regard to HRQoL data, response rates in this study were much higher than previously reported at all candidate follow-up time points 37 ; the lowest response rate of 58⋅3 per cent was observed at 12 months. Data from qualitative patient interviews suggested that the burden of questionnaire completion was high and some questionnaires were deemed irrelevant to the patients' clinical status.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…LaCeS has demonstrated that it is possible to collect high-volume, good-quality clinical and patient-reported outcome data in the emergency setting both at baseline and during follow-up. Although attrition was noted during follow-up with regard to HRQoL data, response rates in this study were much higher than previously reported at all candidate follow-up time points 37 ; the lowest response rate of 58⋅3 per cent was observed at 12 months. Data from qualitative patient interviews suggested that the burden of questionnaire completion was high and some questionnaires were deemed irrelevant to the patients' clinical status.…”
Section: Discussioncontrasting
confidence: 87%
“…The routine collection of patient‐reported outcome data in the emergency setting was previously documented to be of low quality, with poor reporting of baseline data 36 . This is coupled with high rates of attrition, with Mason and colleagues 37 reporting 6‐week response rates of 48·4 per cent, despite an initial baseline compliance rate of 93 per cent among 156 patients presenting to emergency general surgery services. LaCeS has demonstrated that it is possible to collect high‐volume, good‐quality clinical and patient‐reported outcome data in the emergency setting both at baseline and during follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that with high response rates, any responder bias is slight and will not undermine comparisons of providers. The higher response rates achieved in our study compared with a prior study in England 9 may reflect the severity of emergency laparotomy as a subset of emergency surgical admissions. In elective surgery, higher response rates are observed with major procedures such as hip replacement than minor procedures such as inguinal hernia repair.…”
Section: Discussioncontrasting
confidence: 73%
“…The relevance of the available evidence is unclear as studies either involved only a few centres or were restricted to protocol-driven intervention trials instead of routine use. 9 10 In addition, studies were mostly conducted in other countries, so the results may not be applicable in England. 11–18 Response rates ranged between 51% and 71% for mailed questionnaires, and between 51% and 84% for interviewer-administered questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…These are compounded in the emergency surgical setting, with particular challenges to recruitment and data collection. Although little is known about how to optimize data collection in this setting, a recent study has examined the feasibility of collecting patient‐reported outcome data during unplanned hospital admissions. It found that, with specific research support during the working week, good baseline response rates to questionnaires could be achieved.…”
Section: Discussionmentioning
confidence: 99%